2022
DOI: 10.22271/fish.2022.v10.i4c.2713
|View full text |Cite
|
Sign up to set email alerts
|

Growth, exploitation parameters and sexual maturity of Chrysichthys nigrodigitatus (Lacépède, 1803) downstream of the Taabo dam (Bandama River, Côte d’Ivoire)

Abstract: The objective of the present work is to study the growth, exploitation parameters and the size of first sexual maturity of Chrysichthys nigrodigitatus (Lacépède, 1803) landed in N'dènou, in order to evaluate the status of its stock. A total of 7635 fish were sampled monthly from November 2019 to October 2020. The individuals were measured, weighed and the data processed with the FiSAT II software. The calculated parameters are: allometry coefficient (b = 2.77); asymptotic length (L∞ = 51.98 cm); growth coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The growth performance index, Ø exhibit close values within species and closely related taxa. This is similar to the result of Kone et al (2022) andkongbeh et al, (2015) for C. nigrodigitatus in diferent locations in Africa. For the close species, Chrysichthys auratus, growth performance index was 2.55 (Abdellatif et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The growth performance index, Ø exhibit close values within species and closely related taxa. This is similar to the result of Kone et al (2022) andkongbeh et al, (2015) for C. nigrodigitatus in diferent locations in Africa. For the close species, Chrysichthys auratus, growth performance index was 2.55 (Abdellatif et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This implies that the higher the growth coefficient the faster the silver catfish approaches the asymptotic length. The Asymptotic length in this study is greater than those found for the same species by Kone et al (2022), Kongbeh et al (2015, but closer to Ajagbe et (2021). The implication is that Fish with a smaller asymptotic length may initiate reproduction earlier, potentially allowing them to support a larger biomass in comparison to individual with larger length (Ahti et al, 2022).…”
Section: Discussionsupporting
confidence: 82%